The Effect of Eight Weeks of Aerobic Exercise on Interleukin- 6, Insulin Resistance and Blood Glucose of Overweight Female - Masumeh Esmaili Alamdari; Mehrdad Fathi; Nahid Bije; Elham Pouryamehr (Islamic Azad University, 2016)
Introduction: The important factors in the development of chronic diseases are obesity and overweight. The purpose of this study was to investigate the effect of eight weeks aerobic training on interleukin- 6, insulin resistance and glucose in overweight young girls. Methods: Twenty-one girls with an age range of 20-30 years were selected voluntarily and randomly divided into experimental (n = 11) and control (n = 10) groups. The aerobic exercise program lasted for 8 weeks, with a frequency of 3 sessions per week, with training sessions starting from 30 minutes in the first session and 50 minutes in the final session, and the intensity of 60-70% of the heart rate reserve. The blood sample was taken before beginning the main study program. The independent sample t-test, paired sample t- test and the Kolmogorov-Smirnov test were used to compare the pre-test and post-test information between the groups. Results: Eight weeks of aerobic exercise had no significant effect on body mass index (p=0.43), fat percent (p=0.72), waist to hip rate (p=0.85), interleukin- 6 (p=0.86), insulin resistance (p=0.59) and glucose (p=0.78) nevertheless significantly reduced the weight (p=0.004). Conclusion: It appears that eight-week aerobic exercise program could be beneficial for weight loss, but it did not affect glucose concentration, insulin resistance, interleukin- 6 serum, fat percentage, waist to hip ratio and BMI.